Combining the Pharmaceutical and Toxicological Properties of Selected Essential Oils with their Chemical Components by GC‐MS Analysis - Nilofar; Ahmed, Shakeel; Zengin, Gokhan; Di Simone, Simonetta Cristina; Acquaviva, Alessandra; Libero, Maria Loreta; Chiavaroli, Annalisa; Orlando, Giustino; Tacchini, Massimo; Di Vito, Maura; Menghini, Luigi; Ferrante, Claudio (Chemistry & biodiversity, 2024)
In the current investigation, a comprehensive analysis was carried out on essential oils (EOs) extracted from six aromatic plant species, namely Rosmarinus officinalis, Pelargonium graveolens, Thymus vulgaris, Origanum vulgare, Laurus nobilis, and Aloysia citrodora. An exploration was conducted into the chemical composition using Gas Chromatography‐Mass Spectrometry (GC/MS), antioxidant properties assessed through DPPH, ABTS, CUPRAC, FRAP, MCA, and PBD assays, ecotoxicological impacts evaluated via allelopathy and the Daphnia magna heartbeat test, as well as bio‐pharmacological effects including anticancer activity and gene expression analysis. Results revealed strong antioxidant activity in all essential oils, with T. vulgaris EO (2748.00 mg TE/g) and O. vulgare EO (2609.29 mg TE/g) leading in CUPRAC assay. R. officinalis EO showed the highest α‐amylase inhibition at 1.58 mmol ACAE/g, while O. vulgare EO excelled in α‐glucosidase inhibition at 1.57 mmol ACAE/g. Additionally, cytotoxic effects were evaluated on human colorectal cancer (HCT116) cells. A. citrodora, O. vulgare, and R. officinalis EOs were found the most potent anticancer, as also witnessed by their higher modulatory effects on the gene expression of BAX and Bcl‐2. Collectively, the present data highlight the importance to implement the knowledge and to valorize the supply chain of aromatic plants.